Cyclic and post-cyclic behaviour from sand–geogrid interface large-scale direct shear tests. Issue 2 (26th October 2015) - Liu, F.-Y.; Wang, P.; Geng, X.; Wang, J.; Lin, X.
Abstract : The understanding of cyclic and post-cyclic behaviours of the soil–geosynthetic interface is essential for the design of geosynthetic- reinforced soil structures under repeated loads, such as those induced by traffic, earthquakes and compaction. In this paper, a series of monotonic direct shear tests and cyclic direct shear integrating monotonic direct shear tests were conducted by using a large-scale direct shear testing device. The effect of normal stresses, cyclic shear amplitude and cycle number on the post-cyclic behaviour of the interface are investigated. In addition, the influence of cyclic shear on interface direct shear behaviour was discussed in detail. The test results indicated that both the peak and residual shear stresses of the interface during the post-cyclic shear phase increased linearly with normal stress and the number of cycles. The volume contraction, which was induced by the direct shear, decreased with the increase in normal stress. The interface apparent adhesion and friction angle increased with the cyclic shear.